Non-surgical treatment of peri-implantitis with the adjunctive use of an 810-nm diode laser - Roncati, Marisa (Medknow Publications & Media Pvt Ltd, 2013)
An 810-nm diode laser was used to non-surgically treat a 7-mm pocket around an implant that had five threads of bone loss, BoP+, and exudate, and the patient was followed up for 5 years. Non-surgical treatment, home care reinforcement, clinical indices records, and radiographic examination were completed in two consecutive 1-h appointments within 24 h. The patient was monitored frequently for the first 3 months. Subsequently, maintenance debridement visits were scheduled at 3-month intervals. The patient had a decreased probing pocket depth and a negative BoP index compared to initial clinical data, and the results were stable after 1 year. After 5 years of follow-up visits, there appeared to be rebound of the bone level radiographically. Within the limits of this case report, conventional non-surgical periodontal therapy with the adjunctive use of an 810-nm diode laser may be a feasible alternative approach for the management of peri-implantitis. The 5-year clinical and radiographic outcomes indicated maintenance of the clinical improvement.